'Relapse' of chronic active hepatitis--not always what it seems. Issue 849 (July 1996) - Muller, A. F.; Toghill, P. J.; Smith, P.
Abstract : Immune chronic active hepatitis is a disease notorious for its unpredictability. In a patient with chronic hepatitis who has already suffered relapses a search for a second cause of jaundice is not usually necessary. This report emphasises the essential role of liver biopsy.